Effect of calcium silicate hydrate – polycarboxylate ether (C-S-H–PCE) nanocomposite as accelerating admixture on early strength enhancement of slag and calcined clay blended cements. (May 2019) - Kanchanason, V.; Plank, J.
Abstract: The effectiveness of a self-synthesized C-S-H-PCE nanocomposite on early strength development of slag and calcined clay blended cements (35 wt% slag or calcined clay) was studied. Addition of C-S-H-PCE was found to substantially increase mortar strength at early ages, particularly after 6–24 h of curing. Isothermal heat flow calorimetry and in-situ XRD measurements indicate that silicate hydration in cement is significantly accelerated. Most remarkably, C-S-H-PCE also speeds up the pozzolanic reaction of slag and calcined clay and stimulates the formation of hemicarbo aluminate (Hc), especially in calcined clay cement. Thus, C-S-H-PCE can foster more widespread use of CEM II/III. Graphical abstract: Unlabelled Image Highlights: C-S-H–PCE increases early strength (0–24 h) of blended cements. Cements blended with slag or calcined clay (35 wt%) were tested. The nanocomposite accelerates cement hydration by providing C-S-H seeds. Moreover, the pozzolanic reaction of slag and calcined clay is accelerated. C-S-H-PCE also stimulates the formation of Hc in the calcined clay cement.